The Relationship Between Students' Attitudes Towards Violence Against Women And Their Depression - Çetin, Nurdilan Şener; Yılmaz, Ayşe Nur; Kargın, Maral (My University, 2024)
Background: Violence against women, especially by an intimate partner in its various forms (sexual, physical, or stalking), and childhood violence (sexual or physical) are common and are associated with depressive symptoms. Method: The sample of this descriptive-analytic research was consisted of 895 students attending to the Faculty of Health Sciences of a public university in the East of Turkey. Data were collected between October and November 2021 via the \"Personal Description Form\", \"ISKEBE Attitudes Towards Violence Against Women Scale\" and \"Beck Depression Scale\". Descriptive statistics, independent group t-test, Pearson correlation analysis, Chi-square, and ANOVA tests were used for statistical analysis. Results: More than half of the students (56.1%) stated that they were exposed to violence. Verbal violence was reported to come from mothers (24.5%), fathers (20.0%) and sibling (20.2%). In addition, 23.2% of the students experienced emotional violence from their friends and 14.7% from their partners. The majority of participants indicated that an apology typically follows an act of violence as a means of restoring peace and order (28.3%). Attitude towards the body sub-dimension of ISKEBE was significantly related with the exposure to violence in general, experience of emotional and sexual violence, gender, grade and mother's educational level. Beck Depression Scale scores were significantly higher in students exposed to violence, were married, were in first grade and those under the18 years of age Conclusion: In this study, we found that as the age of the students increased, their attitudes towards violence against women became increasingly positive. The depression score of the students who had been exposed to violence at any point in their lives was found to be higher than those who had not experienced violence. Furthermore, it was observed that while students' depression scores increased, ISKEBE scores decreased. This indicates that individuals with elevated depression scores tend to adopt a positive approach to the issue of \"violence against women\". Nurse educators and nurses should plan interventions to protect the mental health of nursing students and to increase their awareness of violence against women.
Keywords: Depression; student; women; Violence; violence against women